I'm having a bit of trouble with this problem.
Solve the equation.
Here is an image of the problem if the equation above is not clear http://i1198.photobucket.com/albums/...g?t=1297473401
Follow Math Help Forum on Facebook and Google+
Is this for an online quiz?
No, just practice.
Ok, that's fine. What ideas have you had so far?
Clearing out the denominators by multiplying the whole equation by (2x) (x+1) x(3x+3)
Go for it; that idea sounds good. Post what you get, and we can help you from there.
After multiplying by (2x) (x+1) x(3x+3) and simplifying I get 3x^3+12x^2+9x=2x^2+2x. This is the part where I'm sort of lost; I'm not sure if I made a mistake or not.
No mistakes so far. Notice that every single term has an x in it. Since x = 0 is not a solution of the original equation (you'd divide by zero in the first term!), you can cancel a power of x from every term. What do you suppose you could do next?
By canceling a power of x from every term do you mean just taking an x out of every term? So 3x^3-10x^2+7x=0 would be 3x^2-10x+7=0?
Exactly. Then what?
Could I use the quadratic equation at this point?
Sure, why not? What's the result?
Using the quadratic equation and substituting 3=a, -10=b and 7=c I get x=7/3 and x=6/6 (1)
I think your answers are off by a minus sign. If you're ever in doubt, plug your solutions back into the equation and see if they satisfy it.
Using 3x^2-10x+7 in the quadratic formula I get x= 10(plus or minus) 4/6 Is that right or did I make a mistake before that?
View Tag Cloud